From Campus to Crime: Unveiling the Link Between Graduate Unemployment and Social Crimes in Lagos, Nigeria: From Campus to Crime - Oni, Adesoji A.; Orutugu, Ikioye L (Lavai - International Journal of Education, 2025)
This study explores the relationship between unemployment and social crimes among university graduates in the Kosofe Local Government Area of Lagos State. The research aimed to answer five key questions and tested corresponding hypotheses. An ex-post facto design was adopted, with a sample drawn from the population of young people in Kosofe. The sample of 400 individuals was selected through purposeful sampling from locations such as bars, betting centres, and okada rider parks. Data was collected using a self-structured questionnaire, the USCG (Unemployment and Social Crimes Graduate) questionnaire, which was validated through face validity. A pilot study in the Ikorodu Local Government Area confirmed the reliability of the instrument. The data were analyzed using Pearson Product Moment Correlation and t-test statistical tools. The findings indicated that there is no significant relationship between graduate unemployment and cybercrime, but a significant relationship was found between graduate unemployment and gambling, prostitution, and youth restiveness. Additionally, no significant gender differences in social crimes among unemployed graduates were observed. The study concluded that graduate unemployment contributes to social crimes such as gambling, prostitution, and youth restiveness. Based on these findings, it is recommended that the government create more industries to address graduate unemployment, thereby reducing cybercrime and other associated social crimes.